Characterization and development of aqueous biphasic systems envisioning their application in the purification of nucleic acids - Dinis, Teresa Beatriz Vide (2022)
Non-viral vectors, such as plasmid deoxyribonucleic acid (pDNA), are gaining momentum in gene therapy. However, the pDNA manufacture still requires the development of cost-effective downstream bioprocesses, able to correspond to all requirements of regulatory agencies and to provide high quantities of these biotherapeutics at lower cost. Amongst the possible downstream processes for pDNA, aqueous biphasic systems (ABS) composed of ionic liquids (ILs) were investigated in this thesis, since IL-based ABS allow to circumvent some technical limitations of the traditional polymer-polymer and salt-polymer ABS, namely the lack of tailored extraction performance and improved selectivity. Despite their potential, there is still a deficiency in the investigation of IL-based ABS to purify nucleic acids. Based on the exposed, this thesis starts with the development of a model to predict the formation of IL-based ABS, which will allow their faster analysis and design to a specific application, followed by the characterization of novel IL-based ABS comprising mixtures of polymers or mixtures of ILs towards a better understanding of the mechanisms ruling the ABS formation. These fundamental studies are essential towards the optimization of IL-based ABS as separation strategies. Finally, the implementation of IL-based ABS to purify DNA-based therapeutics was investigated. In this context, a new model, able to predict with good accuracy the formation of IL-based systems, was developed, based on thermodynamic calculation models and information taken from pure ILs. Thereafter, the determined phase diagrams and partition coefficients of the two novel types of IL-based ABS comprising mixtures of polymers or mixtures of ILs allowed to conclude that ABS with mixtures of ILs do not behave as pseudo-ternary systems, contrarily to ABS composed of mixtures of polymers. Based on the tunable character of IL-based ABS, phase-forming components were successfully designed and demonstrated to be able to preserve the DNA stability, while allowing the selective separation of the deoxyribonuclease I (DNase I) enzyme from the target nucleic acid. As evidenced in this thesis, IL-based ABS have the potential to perform “one-pot” extraction, purification and long-term preservation of DNA, being promising candidates to integrate several downstream steps in the pDNA manufacture.